Empirical Dataset on Parenting Styles: Link with Post Millennium Development Goals’ Global Development Agenda - Sumil, Manuel; Sumil Jr., Manuel Ray; Nuwagira, Adoniya; Kibuuka, Muhammad; Nakimuli, Amina; Byabashaija, Deusdedit; Katushabe, Scovia; Mwebesa, Edson; Muhanguzi, Kibs; Kyeyune, Kirabo; Sumil, Novembrieta (International Journal of Sciences: Basic and Applied Research/IJSBAR, 2015)
This study explored the field of parenting to generate empirical data and how it can be linked to post millennium development goals’ global development agenda in the angles of responsible parenthood and teachers’ role in the classroom. The data were elicited through the ex post facto and prospective designs on specific type of parenting style under the parenting dimensions the father and mother were practicing as experienced by 322 students selected through purposive sampling and stratified random sampling by proportional allocation from multisite nursing schools in Cebu City, Philippines. The findings of the study revealed as follows: (1) the parents practiced a combination of the three parenting styles namely, authoritative, authoritarian and permissive; (2) the indifferent style was less experienced by the respondents; (3) the authoritative style of parenting appeared to be the most dominant
Keywords: Behavior management strategies; Parenting styles; Parenting dimensions